FinOps Handbook for Microsoft Azure: Empowering teams to optimize their Azure cloud spend with FinOps best practices - Soni, Maulik (Packt Publishing, 2023)
Establish successful FinOps practice and bring financial visibility to define cost optimization goals and apply learnings to realize savings for your organization. Key Features Build a FinOps team and foster cross-organizational collaboration to optimize costsGain a deep insight into resource usage and rates to unlock the secrets of cost optimizationApply your FinOps expertise to run a successful practice, reinvesting savings into new feature development Book Description To gain a competitive edge in today's unpredictable economic climate, you’ll need to unravel the mystery of saving costs on Microsoft Azure Cloud. This book helps you do just that with proven strategies for building, running, and sustaining repeated cost optimization initiatives across your organization. You’ll learn how to collaborate with finance, procurement, product, and engineering teams to optimize your cloud spend and achieve cost savings that can make a significant impact on your bottom line. The book begins by showing you how to effectively monitor and manage your cloud usage, identify cost-saving opportunities, and implement changes that’ll reduce your overall spend. Whether you're a small start-up or a large enterprise, this book will equip you with the knowledge and skills needed to achieve cost savings and maintain a lean cloud infrastructure. As you advance, you'll find out how to benchmark your current cloud spend and establish a budget for cloud usage. Throughout the chapters, you’ll learn how to negotiate with your cloud provider to optimize your rate, allocate cost for the container, and gain a solid understanding of metric-driven cost optimization. By the end of this FinOps book, you’ll have become proficient in Azure Cloud financial management with the help of real-world examples, use cases, and scenarios. What you will learn Learn FinOps Informe, Optimize and Operate model for Microsoft AzureChoose from Reservations, Savings Plans, and Spot VMs to reduce costDiscover resource waste using provided pre-built workbooksWrite an effective financial business case and build a FinOps strategyRelate what you learned with three real world use caseAccurately forecast future cloud spend and track budgets Who this book is for This book is for cloud governance experts, finance managers, procurement specialists, product developers, and engineering teams looking to get clear and actionable guidance needed to implement all the phases of the FinOps life cycle in the Microsoft Azure context. This book is ideal for anyone with a basic understanding of financial terms, analytics tools, and the Azure cloud.